Detection of Peptides with Different Charges and Lengths by Using the Aerolysin Nanopore. Issue 1 (15th May 2018) - Li, Shuang; Cao, Chan; Yang, Jie; Long, Yi‐Tao
Abstract: The aerolysin nanopore has a high sensitivity for molecular sensing, owing to its super‐narrow diameter and highly charged lumen structure. Here, taking advantages of its high sensitivity, we investigated peptides with comparable size and mass but different charges. Based on the blockade current and duration time, we found that the charge distribution at the entrance of the aerolysin nanopore governs the capture of peptides. Moreover, peptides with the same charge density but different lengths were measured by the aerolysin nanopore. In comparison to the short peptides, longer peptides gave a larger blockade current and a longer duration time. Our findings demonstrate that both the charge and length of peptides affect the translocation process simultaneously, which improve our understanding of peptides' translocation through the aerolysin nanopore and suggest that aerolysin is an excellent candidate for peptides/protein sequencing. Abstract : Lift the blockade : Three negatively charged peptides with different lengths are driven to translocate the aerolysin nanopore inducing three typical current blockades, which perform differences in current amplitude and duration.